Mediasi Kinerja Keuangan pada Hubungan Leverage dan Likuiditas terhadap Penghindaran Pajak - Mardiana Mardiana; Supami Wahyu Setiyowati (El Muhasaba: Jurnal Akuntansi, 2024)
Purpose: Tax avoidance is a strategic approach aimed at reducing the tax burden while staying within the boundaries of applicable regulations. The objective of this study was to examine how leverage and liquidity influence tax avoidance, with financial performance acting as an intermediary factor.